Determinants of home delivery among reproductive age women in Bore District, East Guji Zone, Ethiopia: a case-control study - Beka Teressa; Elsabeth Legesse; Tadesse Nigussie; Berhanu Senbeta Deriba; Ararso Hordofa Guye; Derara Girma; Hiwot Dejene; Leta Adugna; Belete Birhanu; Hana Eshetu; Amanu'el Tadele; Gachena Mideksa (Frontiers Media S.A., 2024)
IntroductionHome delivery, which is the process of childbirth at one's residence rather than in a health facility, is a major reason for maternal mortality caused by obstetric complications, such as sepsis, hypertensive disorders, and hemorrhage. Maternal and child mortality remains high in developing countries despite efforts made to reduce these outcomes. This is mainly due to poor utilization of institution-based healthcare services. Moreover, there is a limited number of studies that have addressed the determinants of home delivery in Ethiopia, including the study area. This study aims to identify the determinants of home delivery in Bore District, East Guji Zone, Southern Ethiopia, in 2022.MethodsA community-based unmatched case-control study was conducted from 18 May to 5 July 2022 among 498 women (249 cases and 249 controls) who gave birth in Bore District. The case group included women who gave birth at home, while the control group included those who gave their last birth at health institutions. A multistage sampling technique was employed to select the study participants. Data were collected using the KoboToolbox digital software and exported to SPSS Version 26.0 for analysis. A multivariable logistic regression analysis was done to declare the statistical significance of the association of the the independent variables and home delivery.ResultsThe study included a total of 496 respondents with a mean age of 32.5 (SD = ±5.5) for the case group and 33.7 (SD = ±5.2) for the control group. Among the assessed determinants of home delivery were not attending antenatal care (ANC) visits [adjusted odds ratio (AOR) =  5.6, 95% CI: 2.0-15.16], missing pregnant women's conferences (AOR = 3.2, 95% CI: 1.65-8.32), not receiving health education on pregnancy-related complications (AOR = 2.2, 95% CI: 1.1-4.3), inadequate knowledge of pregnancy-related danger signs (AOR = 6.0, CI: 3.0-11.9), inadequate knowledge about pregnancy-related complications (AOR = 3.0, CI: 1.55-6.13), and unfavorable attitude (AOR = 6.9, 95% CI: 2.16-22.6).ConclusionIn this study, not attending ANC visits, missing pregnant women's conferences, not receiving health education on pregnancy-related complications, inadequate knowledge of pregnancy-related danger signs, inadequate knowledge about pregnancy-related complications, and unfavorable attitudes were identified as determinants of home delivery. The district health office and other stakeholders should work on strengthening maternal health service delivery through appropriate ANC visits and participation in pregnant women's conferences and improving community awareness about pregnancy at all levels.